Doping Fe-based diamond tool matrix composites with a rare-earth element - Zou, Q.; Gong, W.; Zeng, X.; Wu, Y.; Liu, J.; Zou, Sh. (Сверхтвердые материалы, 2009)
The paper presents the experiments on adding rare-earth element cerium to diamond matrix composites. Based on the doping of rare earth in metal powders including tungsten carbide, a small amount of nickel, iron entirely replacing cobalt in diamond matrix and the process route of rare earth doping is indicated. The performance of matrix composites with and without rare-earth elements has been assessed. The results obtained show that the flexural strength, the hardness, and the impact ductility of matrix composites with rare-earth elements have been improved. The flexural strength and the impact ductility increased correspondently by 10—62 % and about 5 %, as compared to composites free of rare-earth elements. Rare-earth diamond tool matrix composites where Co was replaced with Fe, which provides a good practical service performanc, and a low price, have been successfully studied, corresponding diamond bits and saw blades have been manufactured.